If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + 3)(3x + 2) = 0 Reorder the terms: (3 + 4x)(3x + 2) = 0 Reorder the terms: (3 + 4x)(2 + 3x) = 0 Multiply (3 + 4x) * (2 + 3x) (3(2 + 3x) + 4x * (2 + 3x)) = 0 ((2 * 3 + 3x * 3) + 4x * (2 + 3x)) = 0 ((6 + 9x) + 4x * (2 + 3x)) = 0 (6 + 9x + (2 * 4x + 3x * 4x)) = 0 (6 + 9x + (8x + 12x2)) = 0 Combine like terms: 9x + 8x = 17x (6 + 17x + 12x2) = 0 Solving 6 + 17x + 12x2 = 0 Solving for variable 'x'. Factor a trinomial. (3 + 4x)(2 + 3x) = 0Subproblem 1
Set the factor '(3 + 4x)' equal to zero and attempt to solve: Simplifying 3 + 4x = 0 Solving 3 + 4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 4x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 4x = 0 + -3 4x = 0 + -3 Combine like terms: 0 + -3 = -3 4x = -3 Divide each side by '4'. x = -0.75 Simplifying x = -0.75Subproblem 2
Set the factor '(2 + 3x)' equal to zero and attempt to solve: Simplifying 2 + 3x = 0 Solving 2 + 3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 3x = 0 + -2 3x = 0 + -2 Combine like terms: 0 + -2 = -2 3x = -2 Divide each side by '3'. x = -0.6666666667 Simplifying x = -0.6666666667Solution
x = {-0.75, -0.6666666667}
| x+6x-1=90 | | (4x-3)*(3x-2)=0 | | 3(2q+3)=5(2q+1) | | -log(x)=20 | | 4x^2+3x+12=12 | | 3(5c-1)-2=13c+13 | | 5x/6-2=3 | | -3x+23=x+3 | | 60x+70y=4200 | | 3(5x-3)-3(2x-5)= | | A-(-3)=25 | | sin(40)=12/x | | y/-9=4 | | x^6-2x^3-4=0 | | 19m+23n+-3n= | | 2x-27=312 | | 7x-19+3x+9=180 | | -(5x-3)-3(2x-5)= | | (4x-6)/3=-2 | | 6*8*18= | | 0.49=cos(x) | | -7(3p+2)40=3(5p+6) | | 18*14*2= | | 5x+32=67 | | N/25-7=-82 | | 3x-2+7+3x-2+7=133 | | -9-5+2-8-9= | | 4x+6+x=180 | | 67y=45n+13 | | 2448/48=x | | X(x-8)=x^2+5x | | 0=40-(1.1xd) |